2021
DOI: 10.1161/circulationaha.121.055524
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Opioid Use After Cardiac Implantable Electronic Device Procedures

Abstract: Background: Prescription opioids are a major contributor to the ongoing epidemic of persistent opioid use (POU). The incidence of POU among opioid-naïve patients after cardiac implantable electronic device (CIED) procedures is unknown. Methods: This retrospective cohort study used data from a national administrative claims database from 2004 to 2018 of patients undergoing CIED procedures. Adult patients were included if they were opioid-naïve during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As a matter of fact, Markman et al showed that the incidence of POU in even opioid-naive patients can be as high as 12%, and therefore a multimodal pain approach, including truncal blocks, is recommended to reduce opioid use in these patients. 20 In addition, recent studies have shown that even a small reduction in intraoperative opioid use can yield a significant decrease in postoperative complications, particularly in high-risk patients, 21 , 22 although large studies are needed to determine this effect.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, Markman et al showed that the incidence of POU in even opioid-naive patients can be as high as 12%, and therefore a multimodal pain approach, including truncal blocks, is recommended to reduce opioid use in these patients. 20 In addition, recent studies have shown that even a small reduction in intraoperative opioid use can yield a significant decrease in postoperative complications, particularly in high-risk patients, 21 , 22 although large studies are needed to determine this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription opioids after surgery including heart implantation became the major contributor to the opioid epidemic (Puymirat et al, 2016). A study demonstrated that approximately 12% of patients continued using opioids even after 30 days of surgery (Markman et al, 2021). In 2017, the Department of Health and Human services declared an opioid epidemic in the United States.…”
Section: Telehealth and Mobile Health (Mhealth) For Cvdmentioning
confidence: 99%
“…Opioids and endogenous derivatives including endorphins exert potent activities within the central, and peripheral nervous systems and subsequently regulate blood pressure, heart rate, and thermogenesis (Bellandi et al, 2016). Thus, postoperative opioid use should be restricted and regulated by multimodality approaches including patient education and being replaced with nonopioid analgesics (Markman et al, 2021).…”
Section: Telehealth and Mobile Health (Mhealth) For Cvdmentioning
confidence: 99%
“…We have recently shown that persistent opioid use is common after cardiac implantable electronic device (CIED) procedures, despite the perception that these are minimally invasive procedures with low periprocedural pain levels. 4 A prescribed dose >135 mg oral morphine equivalents (OME) after CIED procedures is associated with increased risk of persistent opioid use. In this study, we investigated the trends in opioid prescriptions after CIED procedures from 2004 to 2020 with a focus on whether regulatory guidelines have achieved their intended effects.…”
mentioning
confidence: 99%